1995
DOI: 10.1111/j.1432-1033.1995.tb20380.x
|View full text |Cite
|
Sign up to set email alerts
|

Copper Binding to Rabbit Liver Metallothionein

Abstract: Circular dichroism and ultraviolet absorption spectral data have been used to probe the binding mechanism for formation and the structure of the copper(1)-thiolate binding clusters in rabbit liver metallothiionein during addition of Cu' to aqueous solutions of Zn,-metallothionein 2 and Cd,Zn,-metallothionein 2. Mammalian metallothionein binds metals in two binding sites, namely the a and P domains. Spectral data which probe the distribution of Cu(1) between the two binding domains clearly show that both the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
68
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 47 publications
(37 reference statements)
9
68
0
Order By: Relevance
“…Similar to our observations, Neurospora Cu-MT has negative CD at 290 nm and positive CD at 360 nm (32). Moreover, mixed Zn-Cu MTs have positive CD features at 360 nm and negative ones at 280 nm that depend on total metal and Cu∕Zn ratio (30). In MTs, the signals are proposed to arise from d 10 − d 10 interactions of adjacent metal ions when the metal-metal distances are relatively short (i.e., <2.8 Å) (33).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Similar to our observations, Neurospora Cu-MT has negative CD at 290 nm and positive CD at 360 nm (32). Moreover, mixed Zn-Cu MTs have positive CD features at 360 nm and negative ones at 280 nm that depend on total metal and Cu∕Zn ratio (30). In MTs, the signals are proposed to arise from d 10 − d 10 interactions of adjacent metal ions when the metal-metal distances are relatively short (i.e., <2.8 Å) (33).…”
supporting
confidence: 78%
“…This conclusion is based on the highwavelength CD signals (around 350 nm) that match signals found in multi-metal-cluster MTs (30,31). It is possible that the folded Cu-cisPt-Atox1 complex is not monomeric but may to some degree resemble a recently reported Mo-Cu-Atx1 complex (47), formed when the copper-depleting drug tetrathiomolbydate was added to the yeast Cu chaperone, Atx1.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…At present, the precise structure of this species is unknown. Rearrangement of Zn 6 MT-2, perhaps with the formation of two Zn 3 clusters, might occur because the coordination of MT is quite flexible as demonstrated for copper MT, where an MT species containing one Cu 6 S 9 and one Cu 6 S 11 unit has been reported (28). MT exhibits high structural flexibility, and cadmium exchange inside the ␤-cluster and between the ␤-clusters of two MT molecules is fast (29).…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that CisPt can bind to Atox1 in vitro, both in the absence and the presence of Cu [10]. When Cu was pre-bound to Atox1, CisPt binding resulted in the appearance of circular dichroism (CD) signals above 300 nm, likely originating from metal-metal interactions [11][12][13]. Thus, CisPt binding to Cu-Atox1 resulted in a ternary CisPt-Cu-Atox1 complex.…”
Section: Introductionmentioning
confidence: 99%